Social Assistance Recipient Decision Support System with AHP and MOORA - Setiawan Adi Nugroho,; Nur Wakhidah, (Jurnal Transformatika, 2025)
Poverty is a multidimensional problem that requires prompt and appropriate handling to maintain a dignified human life. In Manyaran Sub-district, Semarang City, the distribution of social assistance often faces obstacles due to limited human resources and a manual selection process for recipients. Therefore, a Decision Support System (DSS) is needed to assist the selection process in a more objective and efficient manner. This study aims to develop a DSS for determining social assistance recipients in Manyaran Sub-district by combining the Analytic Hierarchy Process (AHP) and Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) methods. AHP is utilized to determine the weight of each criterion, while MOORA is used to calculate the final score of each recipient candidate. The results show that among the ten analyzed candidates, the individual coded P09 achieved the highest final score of 0.575. The top five candidates with the highest scores were declared eligible to receive social assistance, while the others were declared ineligible. The application of the AHP and MOORA methods in this DSS effectively improves the accuracy, objectivity, and efficiency of the selection process for social assistance recipients in Manyaran Sub-district.